Green IT for dummies - Baroudi, Carol (--For dummies., 2009)
"Green technology is not only good for the environment; it's also good for your bottom line. If your organization is exploring ways to save energy and reduce environmental waste, Green IT For Dummies! can help you get there. This guide is packed with cost-saving ways to make your company a leader in green technology. The book is also packed with case studies from organizations that have gone green, so you can benefit from their experience. You'll also learn what to beware of when developing your green plan, and get familiar with all the terms relating to green IT. Green IT For Dummies starts you on the road to saving money while you help save the planet"--Resource description page.